Chemistry for Changing Times / Third Edition - Hill John W (Burgess Publishing Company, 1980)
This book introduces important concepts and ideas in chemistry and tells you how they relate to daily life. Chemistry: A Science for All Seasons, Atoms: Are They for Real?, Atomic Structure: Images of the Invisible, The Nucleus: Getting to the Heart of Matter, Chemical Bonds: The Ties That Bind, Names and Formulas and Equations: You and Too and Can Speak Chemistry, Acids and Bases: Please Pass the Protons, Oxidation and Reduction: Burn and Unburn, Chemistry of the Earth: The Materials Crunch, Carbon and Hydrocarbons: A Storehouse of Energy, Organic Chemistry: Some Hors d' Oeuvres, Energy: The Chemical Century, Energy for the Future: After Fossil and Fissile Fuels Fizzle, Polymers: Giants Among Molecules, Farm Chemistry: Food for a Hungry World, Food: Those Incredible Edible Chemicals, Food Additives: Bane or Blessing? Water: To Drink or to Dump Our Wastes in, Air: Breath of Life...or Death?, Household Chemicals: Helps and Hazards, Cosmetics: The Chemistry of Charm, Body Chemistry: Drugs - From Colds to Cancer, Chemistry of the Mind: Remedies and Recreation, Index.